Use of a Bone Graft Drill Harvester to Create the Fenestration During Arthroscopic Ulnohumeral Arthroplasty - Malin D. Wijeratna, B.Sc.(Hons), M.B.B.S., F.R.C.S.(Tr&Orth); Eugene T. Ek, M.B.B.S., Ph.D., F.R.C.A.S.; Gregory A. Hoy, M.B.B.S., F.R.C.A.S.; Ash Chehata, M.B.B.S., F.R.C.A.S. (Arthroscopy Techniques, 2015)
The Outerbridge-Kashiwagi procedure, or ulnohumeral arthroplasty, was described in 1978 as a method of treating elbow arthritis by creating a fenestration in the olecranon fossa. This fenestration diminishes the likelihood of recurrent spurs in the olecranon fossa and coronoid fossa, without loss of structural bony strength. Arthroscopic techniques have now been developed to perform this procedure. We describe an efficient method of creating the fenestration between the olecranon fossa and coronoid fossa during an arthroscopic ulnohumeral arthroplasty, or Outerbridge-Kashiwagi procedure, that also reduces the amount of residual bone debris produced during the resection.